SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU BERPRESTASI DENGAN MENGGUNAKAN METODE MOORA - Layuk, Lapu Tombi; Aisya, Nurul (JURNAL INFORMATIKA, 2022)
Assessment of teacher performance at SMP Negeri 2 Bontang has not been carried out optimally, especially in assessing teacher performance. Teacher performance is only determined by their work, there are no clear assessment criteria. Therefore, in this study a teacher assessment will be developed based on competency, which can accommodate teacher performance. The purpose of this study was to design a decision support system using the Moora method to evaluate the performance of teachers at SMP Negeri 2 Bontang. The method used is the moora method which is applied to a decision support system to carry out the selection process for outstanding teachers. In determining the outstanding teachers, first determine the value in each aspect and determine the weighting of each sub-criteria on each criterion. The results of the system design show that the application of the Moora method to the achievement teacher assessment system at SMP Negeri 2 Bontang can provide objective decision results for 49 teachers. In the calculation process, the Moora method provides 4 preference criteria to be used by decision makers, namely training scores, attendance, seminar scores, and achievements. Selection of Preferences because it can be changed according to the needs of the criteria.